Effect of Qingre Lishi decoction on anthropometric and metabolic risk indices in obese patients with newly diagnosed T2DM: a real-world observational study - Wei, Bingchen; Gao, Tianshu; Liu, Qingyang (Frontiers in Endocrinology, 2026)
ObjectiveWe have found the Qingre Lishi decoction can effectively reduce blood glucose and mitigates glycemic fluctuations in patients with newly diagnosed type 2 diabetes mellitus (T2DM). However, its influence on body fat distribution and associated metabolic parameters remains underexplored. This study aims to provide more comprehensive and integrated evidence regarding the clinical efficacy of the Qingre Lishi decoction.MethodsWe involved 70 overweight and obese patients with newly diagnosed T2DM between December 2021 and November 2022. Patients were allocated to the observation group (n = 35), who received the Qingre Lishi decoction add lifestyle intervention, or the control group (n = 35), who received lifestyle intervention only. Comparative analyses were included waist circumference (WC), body mass index (BMI), waist-to-height ratio (WHtR), a body shape index (ABSI), body roundness index (BRI), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), lipid accumulation product (LAP), the triglyceride-glucose (TyG) indices, and related indices (TyG-WC, TyG-BMI, TyG-WHtR).ResultsRegarding anthropometric indices, the observation group demonstrated significant reductions in WC, BMI, and WHtR, with the decreases in WC and WHtR being significantly greater than those in the control group (P < 0.05). The novel indices, ABSI and BRI, also showed a significant downward trend in the observation group compared to the controls. In terms of body fat percentage, the observation group exhibited a significantly greater reduction than the control group (P < 0.01). Concerning lipid profiles, TG and LDL-C levels decreased in the observation group, with a significantly larger reduction in LDL-C compared to the control group (P < 0.05). Furthermore, the metabolic risk indices TyG, TyG-WC, TyG-BMI, and TyG-WHtR all decreased significantly in the observation group, and these reductions were markedly superior to those in the control group (P < 0.01).ConclusionThe therapeutic efficacy of the Qingre Lishi decoction in overweight and obese patients with newly diagnosed T2DM is multifaceted, demonstrated by its ability to enhance abdominal fat distribution, lower TG and LDL-C levels, and improve metabolic risk indices (TyG, TyG-WC, TyG-BMI, and TyG-WHtR) for a more integrated patient outcome.